Pengaruh Pengaruh Luas Lahan, Tenaga Kerja, dan Modal Terhadap Produksi Apel di Desa Tulungrejo, Kota Batu - Devin Ananda Dwiardi Saputra; Agus Sumanto (Primanomics : Jurnal Ekonomi & Bisnis, 2022)
Batu City has long been an apple producing area in Indonesia. However, in recent years, the production of apples in Batu City has decreased. This study aims to determine the effect of land area, labor and capital on the amount of apple production in Tulungrejo Village, Batu City. This research is quantitative with data taken from a sample of 79 farmers in Tulungrejo Village. Data were collected by distributing questionnaires and then analyzed using multiple regression analysis which was carried out using SPSS 25 using the classical assumption test and regression tests such as the f test, t test, and determinant coefficients. Simultaneously all independent variables affect the amount of apple production with a Sig value of 0.000 < 0.05. Then partially, only labor (0.027 < 0.05) and capital (0.000 < 0.05) influence apple production.